Analisis Potensi Kawasan Ekowisata Torosiaje di Kabupaten Pohuwato - Dunggio, Renata; Yusuf, Daud; Eraku, Sunarty (-, 2024)
Community-based ecotourism plays a crucial role in developing sustainable tourism. The Torosiaje area in Pohuwato Regency has significant ecotourism potential, with natural resources such as mangrove forests and unique biodiversity. However, previous studies have not thoroughly explored the integration between environmental conservation and local community empowerment. Here, we show that by adopting an ecotourism approach that directly involves the local community, this area can become a leading tourism destination. The study results indicate a high development potential in this area, with challenges such as accessibility and environmental management needing improvement. The implication is that sustainable management and active participation of the local community are essential to support environmental conservation and enhance the economic well-being of the Torosiaje community..